Detecting pneumothorax during cardiopulmonary resuscitation: The potential of defibrillator measured transthoracic impedance - Aurora Magliocca; Donatella De Zani; Giulia Merigo; Marianna Cerrato; Daria De Giorgio; Francesca Motta; Francesca Fumagalli; Davide Zani; Giacomo Grasselli; Giuseppe Ristagno (Resuscitation Plus)
Introduction: Pneumothorax is a potentially life-treating condition that can represents a complication of cardiopulmonary resuscitation (CPR). An increase in the total amount of air within the thorax may act as an insulator increasing transthoracic impedance (TTI). The aim of this study was to evaluate the effects of pneumothorax on TTI and on resuscitation success in a swine model of cardiac arrest (CA) and CPR. Methods: Forty pigs undergoing CA and prolonged CPR, and with a chest CT scan performed after resuscitation were included in the study. Pneumothorax was classified as mild, moderate, or severe whether the space occupied by the gas was <15 %, 15–50 %, or >50 % of the hemithorax. TTI was measured and recorded by the defibrillator before each defibrillation, and the last one was used for the analyses. Rate of return of spontaneous circulation (ROSC) and survival up to 96 h were assessed. Results: Seven (17%) animals had mild-moderate pneumothorax and 10 (25%) severe pneumothorax. Mean TTI was significantly higher in pigs with pneumothorax compared to those without. The rate of ROSC was significantly lower in pigs with pneumothorax compared to those without (53% vs 83%). TTI increased progressively with the size of pneumothorax (mean TTI: 55 O no pneumothorax, vs 62 O mild-moderate vs 66 O severe pneumothorax). Rib fractures were present in all animals with mild-moderate and severe pneumothorax, and in 91% of those without. The total number of rib fractures was significantly higher in animals with severe pneumothorax compared to those without pneumothorax. Conclusion: Pneumothorax causes TTI increases which are proportional to the size of the pneumothorax and ultimately reduce resuscitation success. High prevalence of chest skeletal injuries was observed in this study regardless of the presence of pneumothorax with higher amount of rib fractures in animals with severe pneumothorax. TTI measured by defibrillator can be used to detect the presence of pneumothorax during CPR. Future studies should explore this concept of TTI as a diagnostic tool, in order to improve resuscitation outcome in patients with pneumothorax.